The Establishment of Shelters as a New Paradigm Towards Struggling With Violence Against Women: A Literature Review - Farangis Sharifi; Zahra Hadizadeh Talasaz; Mona Larki (Tehran University of Medical Sciences, 2024)
Objective: Shelters are an important part of a full response to survivors, as stated in many international conventions, such as the 1995 Beijing Declaration and Platform for Action (BDPfA). This study aims to provide a comprehensive perspective on the establishment of shelters for women survivors of violence. Materials and methods: This narrative review was conducted based on the Scale for the Assessment of Narrative Review Articles (SANRA). The MEDLINE, SCOPUS, Web of Science, Embase, Ovid, and EBSCO databases in English and Magiran and Scientific Information Database (SID) in Persian were searched for related documents. Also, WHO, the Joint United Nations Programme on HIV and AIDS (UNAIDS), the Centers for Disease Control and Prevention (CDC), and the United Nations Population Fund's (UNFPA) guidelines and instructions for shelter services for women and girls who have been subjected were searched up to July 31, 2023. A qualitative synthesis was carried out on the 28 eligible articles and instructions out of the 420 retrieved documents. Results: "A "shelter" describes emergency and temporary "safe accommodation for women and children who have been subjected to or are at risk of (typically male) domestic abuse. Types of shelters include emergency shelters or safe homes, second-stage or transitional housing facilities, third-stage housing, and alternative accommodation during (and occasionally after) the period of residence. The shelter delivers a wide range of services, including health services, socio-economic services, and legal services. These principles consisted of a comprehensive perspective, quality of service, organization, funding, and the right issues. Conclusion: Women who are survivors need holistic, interdisciplinary, and specialist care that focuses on safety and needs. The adoption of regulations with robust enforcement guarantees and the facilitation of approvals for the construction of non-governmental shelters and safe houses should be on the agenda setting.